Medical Certification for Utility Shut-Off Protection and Health-Related Social Needs - Rosenberg, Julia; Rosenthal, Alice; Castillo, Suzanne; Edwards, Emily; Erickson, Caroline; Nogelo, Patricia; Fenick, Ada M (Pediatrics (Evanston), 2022)
Children in families facing energy insecurity have greater odds of poor health and developmental problems. In this study of families who requested and received medical certification for utility shut-off protection and were contacted by our Medical Legal Partnership (MLP), we aimed to assess concurrent health-related social needs related to utilities, housing, finances, and nutrition. After medical certificates were completed at our academic pediatric center, our MLP office contacted families and assessed utility concerns as well as other health, social, and legal needs. In this observational study, we present descriptive analyses of patients who received certificates from September 2019 to May 2020 via data collected through the MLP survey during the coronavirus disease 2019 pandemic (June 2020-December 2021). Of 167 families who received utility shut-off protection from September 2019 to May 2020, 84 (50.3%) parents and guardians were successfully contacted. Most (93%) found the medical certificate helpful. Additionally, 68% had applied for Energy Assistance, and 69% reported they were on utility company payment plans. Most (78%) owed arrearages, ranging from under $500 to over $20 000, for gas, electric, and/or water bills. Food, housing, and financial insecurity screening positivity rates were 65%, 85%, and 74%, respectively. Patients who were contacted by an MLP after receiving medical certification for utility shutoff protection were found to have challenges paying for utilities and faced multiple food, housing, and financial stressors. Through consultation and completion of medical forms for utility shutoff protection, pediatricians and MLPs can provide resources and advocacy to support families' physical, emotional, and psychosocial needs.